Prevalence and patterns of workplace cyberbullying among dental and medical undergraduate students. A cross-sectional study - Roopam Kumari; Raj Kishore Prasad; Dilu Davis; Pankaj Bajirao Patil; Basant K. Choudhury; Munaz Mulla; Jagadish Prasad Rajguru (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Cyberbullying is an act of bullying that is conducted through the use of technology in an online mode such as over social media platforms or via text-based messages. It is an intentionally repeated aggressive activity in which harm is inflicted on a person using electronic media. This study aimed to evaluate the prevalence and pattern of workplace cyberbullying in undergraduate students inmedical and dental streams. MATERIALS AND METHODS: This study used a mixed explanatory cross-sectional study design by making use of a structured questionnaire for the survey. This "two-phase" mixed design utilized qualitative data for the explanation of quantitative observations. The selected study subjects were three hundred undergraduate medical and dental students. To obtain data, an electronically fabricated questionnaire (i.e. Google Form) consisting of open- and closed-ended questions was distributed. All questions were designed for studying prevalence and patterns of cyberbullying that had been experienced by the victims. Obtained data were analyzed using Statistical Package for Social Science software version 20.0 (SPSS v20.0) based on a Likert-based questionnaire scale in which responses were recorded in "yes" or "no" format. The statistical tool employed was the "Chi-square" test. RESULTS: On analysis of the level of knowledge, 92% of the study sample was aware of cyberbullying as different from the physical form of bullying. The most commonly employed tools for handling cyberbullying were conferencing (0.66% of cases) and disciplinary tools (5% of cases). 14.33% of cases involved the use of investigations, and 2.66% made use of victim counseling. Most of the students, along with their parents (89%), were of the opinion that teachers must have active participation in cyberbullying cases. On statistical comparison, the P-value was found to be less than 0.05. CONCLUSION: In the present study, cases of cyberbullying were found to be less prevalent in medical and dental undergraduate students although there was knowledge regarding this form of bullying in studied participants.